Modeling and Simulation Analysis of MW-Level Fuel Cell Distributed Generation System Based on AspenPlus - Zhuoyan LI; Liping DUAN; Shaohua LI; Jing FENG (南方能源建设, 2022)
[Introduction] The fuel cell distributed generation technology is an important application direction to adapt to the future development trend of low-carbon, clean and high-efficiency energy. There are few domestic fuel cell power station projects , and there is a lack of actual project experience accumulation. In order to promote the application of fuel cell distributed power station technology, the research outlined the current application status at home and abroad, summarized the advantages and disadvantages of high temperature fuel cells, investigated domestic fuel cell construction and application cases, and established solid oxide fuel cell (SOFC) and molten carbonate fuel cell (MCFC) power generation system processes. [Method] After literature research and field research, two fuel cell distributed generation technologies suitable for the construction of large-scale power stations were identified. Chemical simulation software AspenPlus was used to establish the process model, electrochemical model and energy analysis model for the fuel cell system, and the performance simulation analysis of the system was carried out. [Result] The analysis results show that they are consistent with the actual operation results and the system performance trend predicted by the analysis is consistent with the existing research. [Conclusion] The simulation method can be used in the research of MW-level high-temperature fuel cell distributed generation system, and can provide data support for expanding the application scale of fuel cells.